Effective threat management: a primer - Calhoun, Frederick S. (Routledge, Taylor & Francis Group, 2025)
"Effective Threat Management: A Primer presents the ABCs for identifying, assessing, and managing potentially violent individuals. By offering practical advice and tactics for dealing with problem individuals, the Primer serves as an ideal reference source for threat management professionals and as a practical introduction to threat management best-practices for those new to the field. The question-and-answer format makes finding information easy. The book offers tips and cautions on practical ways to implement an effective threat management program in various situations, such as interpersonal relationships, schools, workplaces, public gathering places, or religious establishments. The Primer emphasizes practical, field-tested approaches to the challenges of identifying, assessing, and managing problem individuals. In the Primer, author Frederick S. Calhoun, a respected expert in threat assessment and management, shows how to set up a threat management process free of elaborate procedures or significant commitments of resources. The Primer offers a practical, step-by-step process for identifying, assessing, and managing problem individuals. Each section answers specific questions. A quick reference guide allows users to quickly locate specific issues or topics. Text boxes throughout the Primer offer practical support, helpful cautions, and real case-study illustrations. This user-friendly book will help threat management professionals in law enforcement and security positions as well as other professionals potentially facing threats, such as mental health practitioners, teachers, HR professionals, small business owners, and anyone else confronted with the need for threat management"--